Optimizing Canva Application Training to Support Teacher Creativity in the Learning System at Al Banin Integrated Islamic School - Retyana Wahrini; Ganggang Canggi Arnanto; Dwi Purnama Soiswaty; Hendra jaya (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
This Community Service (PKM) activity was carried out at Al Banin Makassar Integrated Islamic School with the aim of optimizing the use of the Canva application in supporting teacher creativity in creating interesting, interactive learning materials, and in accordance with the development of educational technology. The background of this activity is based on the need for teachers to adapt learning methods to the digital era, where the use of visual learning media is very important in increasing student interest and understanding. Canva training was provided to teachers as a solution to enrich the ability to design more interesting and effective learning media. The results of this activity show that teachers have become more confident and creative in designing communicative and efficient teaching materials. In addition, this activity also supports the achievement of the Key Performance Indicators (IKU) of higher education. It is hoped that this activity can be the first step in encouraging digital transformation in the school environment, while improving the quality of learning at Al Banin Integrated Islamic School.